PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH PADA MATERI ZAT ADITIF MAKANAN BERKAITAN DENGAN KESEHATAN TERHADAP HASIL BELAJAR KOGNITIF, SIKAP DAN AKTIVITAS SISWA SMP INSHAFUDDIN KOTA BANDA ACEH - Wildan Seni; Annie Kusharyanti; Ema Dauyah (Jurnal Dedikasi Pendidikan, 2023)
This study aims to determine the improvement of students' attitudes towards snacks containing harmful additives for health and student cognitive learning outcomes. In this study, the method of classroom action research (classroom action research) consists of several stages, namely planning, action, observation and reflection. The population in this study were all students of class VIII SMP Inshafuddin Banda Aceh City. The research sample was one class which was randomized by random sampling. Instruments in the form of cognitive ability tests, student attitude scale questionnaires, interview guidelines, observation sheets. The data obtained is processed using the activity criteria that have been determined. The results of this study indicate that, 1) There was an increase in students' attitudes towards snacks containing additives that are harmful to health after the implementation of a problem-based learning process on food additives related to health with an average attitude value of 61% in cycle I and an average of 61%. the average value of the attitude of the second cycle is 83% and the gain value is 56%. 2) There is an increase in learning outcomes in each cycle where in the first cycle 10% of students complete with a classical score of 36.81, in the second cycle 65% of students complete with a classical score of 65.8 and in the third cycle 90% of students complete with a classical score of 80.8 after the application of the process problem-based learning on food additives related to health.